Biopolymer Methods in Tissue Engineering - Hollander, Anthony P.; Hatton, Paul V.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2004)
Because the rapidly developing field of tissue engineering encompasses all the major scientific disciplines-including materials science, polymer chemistry, biology, and medicine-it has often been difficult to uncover the full range of laboratory methods required in tissue engineering. In Biopolymer Methods in Tissue Engineering, expert laboratory researchers bring together in a standard format all the diverse laboratory methods needed to perform state-of-the-art tissue engineering research. Topics range from the synthesis, processing, and characterization of specific biomaterials, through the successful use of scaffolds in the engineering of tissues, to techniques useful in evaluating the biological quality of scaffold-engineered tissues. Subjects of special interest include the incorporation of biological molecules into scaffold biomaterials and the use of a wide range of methods and techniques to generate a comprehensive description of cell-polymer construct quality. Additional techniques can be used to develop effective in vitro models for drug evaluation or to investigate cell and tissue differentiation. Each readily reproducible protocol follows a uniform format that includes essential background information, step-by-step instructions by an expert, equipment and reagent lists, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and state-of-the-art, Biopolymer Methods in Tissue Engineering offers both advanced and novice investigators a diverse collection of readily reproducible techniques for generating living cell-polymer constructs in their laboratories and for evaluating their biological quality.
Processing of Resorbable Poly-?-Hydroxy Acids for Use as Tissue-Engineering Scaffolds -- Fibrin Microbeads (FMB) As Biodegradable Carriers for Culturing Cells and for Accelerating Wound Healing -- Synthesis and Characterization of Hyaluronan-Based Polymers for Tissue Engineering -- Synthesis and Characterization of Chitosan Scaffolds for Cartilage-Tissue Engineering -- Characterization of a Calcium Phosphate-Based Matrix for rhBMP-2 -- Methodologies for Processing Biodegradable and Natural Origin Scaffolds for Bone and Cartilage Tissue-Engineering Applications -- Alginates in Tissue Engineering -- Production and Surface Modification of Polylactide-Based Polymeric Scaffolds for Soft-Tissue Engineering -- Modification of Materials With Bioactive Peptides -- Isolation and Osteogenic Differentiation of Bone-Marrow Progenitor Cells for Application in Tissue Engineering -- Cell Seeding of Polymer Scaffolds -- Chondrocyte Isolation, Expansion, and Culture on Polymer Scaffolds -- Bioreactor Culture Techniques for Cartilage-Tissue Engineering -- Microscopic Methods for the Analysis of Engineered Tissues -- Transmission Electron Microscopy of Tissue-Polymer Constructs -- Application of Microscopic Methods for the Detection of Cell Attachment to Polymers -- Biochemical Methods for the Analysis of Tissue-Engineered Cartilage -- Real-Time Quantitative RT-PCR Assays -- Mechanical Testing of Cell-Material Constructs: A Review.
Keywords: Biomaterials; Biomaterials